2010
DOI: 10.1016/j.neuron.2010.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Decoding a Perceptual Decision Process across Cortex

Abstract: Perceptual decisions arise from the activity of neurons distributed across brain circuits. But, decoding the mechanisms behind this cognitive operation across brain circuits has long posed a difficult problem. We recorded the neuronal activity of diverse cortical areas, while monkeys performed a vibrotactile discrimination task. We find that the encoding of the stimuli during the stimulus periods, working memory, and comparison periods is widely distributed across cortical areas. Notably, during the comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
301
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(353 citation statements)
references
References 43 publications
(65 reference statements)
46
301
0
Order By: Relevance
“…Everything that is known about decision-making in the brain points to awareness as explicitly generated neuronal signals that are received by a decision integrator. A similar point has been made with respect to reportable sensory experience by Romo and colleagues (de Lafuente & Romo, 2005;Hernandez et al, 2010).…”
Section: Tpj Sts Mpfcsupporting
confidence: 66%
“…Everything that is known about decision-making in the brain points to awareness as explicitly generated neuronal signals that are received by a decision integrator. A similar point has been made with respect to reportable sensory experience by Romo and colleagues (de Lafuente & Romo, 2005;Hernandez et al, 2010).…”
Section: Tpj Sts Mpfcsupporting
confidence: 66%
“…1D). We based this selection on the previously described responses of single neurons from these cortical areas associated with different components of the somatosensory discrimination task (7). Examples of the raw simultaneously recorded LFPs during the discrimination task are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed that the neuronal activities distributed across parietal and frontal lobe cortices correlate with processes that lead to decision making (4)(5)(6)(7). However, how these spatially distant, cortical circuits coordinate their activities into a unified functional network during decision making remains poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, other regions beyond IPS are also likely to be involved in sensorimotor transformations. A recent examination of activity across the macaque cortex during a delayed vibrotactile comparison task demonstrated that activity during the first sensory input was found beyond primary somatosensory cortex (S1) in ventral premotor (VPC), medial premotor (MPC), and prefrontal cortex (PFC) (Hernandez et al, 2010). Only those regions outside S1 showed activity correlated with sensory comparisons and motor planning during presentation of the second sensory input.…”
Section: Stimulusmentioning
confidence: 99%